Pediatric Inflammatory Myofibroblastic Tumor of the Liver: A Rare Cause of Portal Hypertension. Issue 3 (March 2019) - Thavamani, Aravind; Mandelia, Chetan; Anderson, Peter M.; Radhakrishnan, Kadakkal
Abstract : ABSTRACT: Hepatic inflammatory pseudotumors or myofibroblastic tumors are benign neoplasms rarely seen in children. We report a case of a previously healthy 10-year-old girl with prolonged fever and abdominal pain who was found to have hepatosplenomegaly and pancytopenia. Imaging revealed a periportal mass along with thrombosis of portal vein and splenomegaly. Liver biopsy showed normal hepatic architecture with no evidence of cirrhosis. She underwent endoscopic banding of esophageal varices. Biopsy of the mass was suggestive of inflammatory myofibroblastic tumor without malignant changes. She has been successfully managed with nonsteroidal anti-inflammatory drug and pulse steroids with resolution of symptoms and decrease in size of the tumor with more than 2 years of follow-up.